Incommunicado detention and torture in Spain, Part I: The Istanbul Protocol Project in the Basque Country: Istanbul Protocol Project in the Basque Country Working Group - Hárdi, Lilla; Morentin, Benito; Inmaculada, Agirre; Inmaculada, Albi; Andueza, Oihana; Miren, Arana; Maitane, Arnoso; Olatz, Barrenetxea; Barrios, Oihana; LF, Callado; Itziar, Gandarias; Eulate, Josefina García de; et al. (Torture Journal, 2018)
There is increasing evidence to show that torture is a serious problem in the Basque Country. Whilst such evidence can be found in reports of international human rights monitoring bodies, sentences of Spanish and international courts, and empirical studies, they are limited in not having followed the Istanbul Protocol (IP) in order to evaluate the reliability of torture. A working group composed of professional associations of psychiatrists, psychologists, physicians, and lawyers, in collaboration with the University of the Basque Country, conducted a four-year study on the medical and psychological consequences of torture in incommunicado detainees, including an assessment of credibility in line with the IP. The methodological design included a multi-level peer-reviewed blind assessment and input by an external expert (from the Independent Forensic Expert Group facilitated by the International Rehabilitation Council for Torture Victims (IRCT)). A sample of 45 Basque people held in short-term incommunicado detention under anti-terrorist legislation (between 1980 and 2012) in Spain who had reported ill-treatment or torture was selected. The findings are divided into four papers: the present introductory paper; the second analyses the credibility of the allegations of torture and introduces an innovative methodology that enhances the IP, the Standardized Evaluation Form (SEC); the third provides an analysis of the methods of torture and introduces the concept of Torturing Environments; and, in the last paper, the psychological and psychiatric consequences of incommunicado detention are analyzed. The collection of papers are intended to be useful not only in the documentation of torture in the Basque Country and Spain but also as an innovative example of how the IP can be used for research purposes.